2021
DOI: 10.3389/fvets.2021.663727
|View full text |Cite
|
Sign up to set email alerts
|

Functional Amino Acids in Pigs and Chickens: Implication for Gut Health

Abstract: In pigs and broiler chickens, the gastrointestinal tract or gut is subjected to many challenges which alter performance, animal health, welfare and livability. Preventive strategies are needed to mitigate the impacts of these challenges on gut health while reducing the need to use antimicrobials. In the first part of the review, we propose a common definition of gut health for pig and chickens relying on four pillars, which correspond to the main functions of the digestive tract: (i) epithelial barrier and dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 156 publications
1
44
0
2
Order By: Relevance
“…Broilers fed corn-based diets are more conducive to Gln supplementation due to lower concentration of Gln in corn relative to wheat particularly when reduced protein diets are used [25]. The positive growth performance by feeding a combination of Gln and Arg may also be explained by their stimulatory effects on gut development (e.g., provision of energy source for enterocytes, synthesis of polyamines), immune response and function, as well as epithelial cells regeneration [2,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Broilers fed corn-based diets are more conducive to Gln supplementation due to lower concentration of Gln in corn relative to wheat particularly when reduced protein diets are used [25]. The positive growth performance by feeding a combination of Gln and Arg may also be explained by their stimulatory effects on gut development (e.g., provision of energy source for enterocytes, synthesis of polyamines), immune response and function, as well as epithelial cells regeneration [2,26].…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids play fundamental roles in the optimum functionality of the intestine with increasing evidence of regulation of intestinal barrier function by concentration of amino acids in the diets [1]. There is evidence for the role of amino acids such as glutamine (Gln), arginine (Arg), and threonine (Thr) having positive effects on controlling Animals 2021, 11, 2416 2 of 17 permeability, promoting cell proliferation, and stimulating several metabolic pathways such as mTOR [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that the red yeast supplementation in laying hen diet benefited the gut health as indicated by increased duodenal histology and cell proliferations. On a cellular level, increased PCNA (protein which increases DNA polymerase activity) and mitotic index are described as indicators of cell proliferation [57]. Investigations in broilers receiving resistant starch (prebiotic property) have observed that duodenal mitotic index (the numerical percentage of PCNA-positive nuclei) was greater in chickens receiving a diet with 12% corn resistant starch than chickens receiving control diet [58].…”
Section: Discussionmentioning
confidence: 99%